Influence of blast furnace gas flow speed on dust deposition characteristics in butterfly valve region - Lixin WANG (Journal of Hebei University of Science and Technology, 2016)
The blast furnace gas contains plenty of dust, which deposits easily on the bottom of seat sealing surface of the tri-eccentric butterfly valve in the pipeline, causing stuck and damage to the valve plate, thereby affects the production of the blast furnace and brings great economic loss. To derive the influence mechanism of effects of the blast furnace gas flow speed within the pipeline on the dust deposition laws in the butterfly valve region, a 3D model of the butterfly valve and its regional flow field is built with Pro/E software. Based on FLUENT module of ANSYS Workbench, along with standard k-ε turbulence model and DPM model, simulation analysis of moving trajectories of dust particles in butterfly valve region under 3 blast furnace gas flow speeds is conducted. Results show that the deposition mass of dust particles decreases firstly, then increases with the enlargement of valve plate opening angle under the blast furnace gas flow speed of 8 m/s, while decreases with the enlargement of valve plate opening under the blast furnace gas flow speeds of 12 m/s and 16 m/s. In the case of the valve plate opening angle of 15°, the deposition rate of dust particles increases with the growing of blast furnace gas flow speed, while decreases with the growing of blast furnace gas flow speed under the cases of valve plate opening angle of 45° and 75°. The research results provide a theoretical reference for the development of automatic dust removal system in the butterfly valve region of the blast furnace gas pipeline.